Pitutur Luhur dalam Novel Cinencang Lawe - Mufakhomah, Ani Nurul; Waluyo, Budi; Rahadini, Astiana Ajeng (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2022)
This research examines the values of kindness in the form of the supreme message of the Javanese contained in the novel Cinencang Lawe, and hence the novel's ability to affect the nation's character. The purpose of this research is to describe the supreme message in Tulus Setiyadi's novel Cinencang Lawe. This researcher utilized a qualitative descriptive method. In this research, there are two sorts of data sources: primary and secondary. The content of the novel Cinencang Lawe serves as the primary data source in this research. Journals, reference books, and the result of informant interviews represent types of secondary data sources. The sample in this research are empirical qualitative data, including passages from the novel Cinencang Lawe, as well as meaningful qualitative data, such as the interpretation of citations obtained from the novel Cinencang Lawe. Purposive sampling was utilized as a sampling method. Content analysis is used as a data collecting tool. The data analysis technique used interactive analysis, which included data collection, data reduction, data display, and verification. The values of the goodness supreme message presented in the novel Cinencang Lawe are the result of this research. The supreme message contains highly noble and amazing cultural values. The values represented in the supreme message can positively impact the nation's character.